1989
DOI: 10.1017/s0952523800012335
|View full text |Cite
|
Sign up to set email alerts
|

The appearance and distribution of microglia in the developing retina of the rat

Abstract: We have examined the development of microglia in the rat retina, using a peroxidase-conjugated lectin derived from Griffonia simplicifolia. Retinas were studied from animals aged from E(embryonic day)12, just after the invagination of the optic cup and prior to the closure of the optic fissure, to adulthood. The lectin also proved a sensitive label for the endothelial cells of the developing retina. Our results provide some support for the view that microglia are derived from the monocyte-macrophage series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
101
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(124 citation statements)
references
References 25 publications
(14 reference statements)
21
101
2
Order By: Relevance
“…At 6 days after birth (P6), obvious abnormalities can be seen in the Nuc1 astrocytes. Confocal microscopy of retinal flatmounts doublelabeled with GFAP and Isolectin B4, which labels blood vessels in the rat (Ashwell et al, 1989), clearly showed changes in process length in Nuc1 astrocytes. The compact stellate astrocyte structure normally seen in the wild-type was missing in the Nuc1 retina.…”
Section: Maumenee Personal Communication)mentioning
confidence: 97%
“…At 6 days after birth (P6), obvious abnormalities can be seen in the Nuc1 astrocytes. Confocal microscopy of retinal flatmounts doublelabeled with GFAP and Isolectin B4, which labels blood vessels in the rat (Ashwell et al, 1989), clearly showed changes in process length in Nuc1 astrocytes. The compact stellate astrocyte structure normally seen in the wild-type was missing in the Nuc1 retina.…”
Section: Maumenee Personal Communication)mentioning
confidence: 97%
“…In the mammalian retina microglial cells appear well before of vascularization (Ashwell et al, 1989;Schnitzer, 1989;Diaz-Araya et al, 1995), and they spread throughout the entire avascular retina of the quail (Navascue s et al, , 1995. Eventually, some microglial cells are seen adhering to or near blood vessels (Murabe and Sano, 1982b;Navascue s et al, 1996;Dalmau et al, 1997a), but microglial cells are not distributed around blood vessels during development, as would be expected if they came from the blood stream.…”
Section: Entry Of Microglial Precursors From the Blood Streammentioning
confidence: 98%
“…Previous investigators have reported the weakening in the intensity and reliability of GS lectin labeling in adult rat retina, making it difficult to quantify microglial numbers in naive control animals. 24 However, despite these difficulties, quantification of GS lectin-positive microglia showed a marked increase in these cells from 12 hours through to day 2 pi. GS lectin-positive microglia had an approximate density of 5 cells/mm 2 in naive controls.…”
Section: Activated T Cells Induce a Limited Breakdown Of The Brb And mentioning
confidence: 99%